PERBEDAAN DUKUNGAN SOSIAL TEMAN SEBAYA PADA SISWA ABK (ANAK BERKEBUTUHAN KHUSUS) DITINJAU DARI JENIS KELAMIN - Ahmad Nur Hidayat; Ima Fitri Sholichah (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: Stigma in society regarding gender is something that has various characteristics, both female and male. Likewise in terms of social support, women who are often considered gentle, and men who are often considered more assertive, can provide social support to ABK (Children with Special Needs) students differently. Objective: The purpose of this study was to empirically determine the differences in Peer Social Support for ABK (Children with Special Needs) Students Reviewed from Gender. Method: This study involved the population of Public Elementary Schools in Surabaya that permitted research with accidental sampling techniques, obtaining 114 respondents. Data was collected using a social support questionnaire and biodata to determine the respondents' gender. Result: Based on the results of the hypothesis testing, the Mann-Whitney test score was obtained with a p-value of 0.209, meaning that there was no significant difference between peer social support for ABK (Children with Special Needs) students of female and male gender. Conclusion: The findings of this study are narrowed down from previous studies, namely here focusing on peer social support.